2004
DOI: 10.1093/jb/mvh040
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of DRG2 Increases G2/M Phase Cells and Decreases Sensitivity to Nocodazole-Induced Apoptosis

Abstract: DRG2, a member of the DRG subfamily in the GTP-binding protein superfamily, was identified as a repressed gene product in fibroblasts transformed by SV40. The significance of this down-regulation and the cellular role of DRG2 has not been understood in the past. To investigate the function of DRG2 we made a Jurkat cell line, Jurkat-LNCX2-DRG2, stably transfected with pLNCX2-DRG2 to overexpress human DRG2. Cell cycle distribution analysis revealed an increased accumulation of G(2)/M phase cells in Jurkat-LNCX2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 17 publications
2
28
0
Order By: Relevance
“…DRG1 and DRG2 comprise a highly conserved subfamily of GTP-binding proteins thought to regulate cell growth [18, 19]. In the present study, we demonstrated that ZC3H15, which interacts with DRG1, is highly expressed in HCC and regulates tumor cell proliferation in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 61%
“…DRG1 and DRG2 comprise a highly conserved subfamily of GTP-binding proteins thought to regulate cell growth [18, 19]. In the present study, we demonstrated that ZC3H15, which interacts with DRG1, is highly expressed in HCC and regulates tumor cell proliferation in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 61%
“…5A). DRG1 has been implicated in regulation of the cell cycle and may be important in growth and differentiation of cells (76).…”
Section: Genes Associated With Cell Cycle Control and Myoblast Prolifmentioning
confidence: 99%
“…Conversely, DRG2 is found to be highly expressed in actively growing tissues and the reproductive organs of Arabidopsis thaliana (mouse-ear cress) (8). Moreover, overexpression of DRG2 caused cell cycle arrest in the G2/M phase (19,32). Collectively, these findings suggest that DRG2 may affect differentiation and activity of OCs.…”
mentioning
confidence: 69%
“…Previous reports suggest that DRG2 plays a critical role in the growth and differentiation of cells (19,32). It is possible that DRG2 modulates the differentiation of OCs, leading to the increased bone resorption and loss observed in the Tg mice.…”
Section: Discussionmentioning
confidence: 96%